Knowledge and attitude of dental school faculties towards stem cell therapies and their applications - Ajlan,Sumaiah; Ashri,Nahid (PeerJ, 2025)
Background Stem cells are characterized by their ability to self-renew and differentiate across multiple lineages. Knowledge about these cells and their potential is an important factor driving people to support their use. Therefore, we aimed to evaluate the knowledge and attitudes regarding stem cell therapies, education, and donation among faculty members of the College of Dentistry at King Saud University, Saudi Arabia. Methods A self-completed questionnaire was distributed among the faculty members, in which questions about demographic data, basic knowledge of stem cells as well as attitudes towards education and participation in stem cell-related research, and tissue donation were raised. Results A total of 102 participants responded to the questionnaire. Most participants (62.7%) ranked their stem cell knowledge as basic, despite correctly answering most of the knowledge questions. More than half of faculty mentioned a lack of stem cell-related activities in their courses (59.8%), and most showed strong support for including related education in postgraduate programs (71.6%). Noteworthy, 64% of participants reported interest in stem cell research and 74.5% were willing to donate their tissue for research purposes. The mean ranks of knowledge scores were significantly higher in subjects who have related lectures in undergraduate courses (p < 0.05), and those with high interest in research participation and tissue donation (p < 0.0001), and (p < 0.05) respectively. Most participants (>60%) were not aware about the current applications of stem cell research and therapy in Saudi Arabia. Conclusion Most participants had an acceptable degree of knowledge about stem cells and showed a positive attitude to their education and participation in research. Additionally, knowledge scores have significantly and positively influenced those attitudes. More effort is required to promote the presence of local facilities for researchers to participate in stem cell-related research. The results of this study can be used as a foundation for evidence-informed policymaking within dental schools and research institutions.
Keywords: Knowledge; Attitudes; Dental faculty; Tissue donation; Graduate; Practice; Dental education; Multipotent stem cells